Openness Can Be Good for Growth: The Role of Policy Complementarities - Chang, Roberto; Kaltani, Linda; Loayza, Norman V. (2012)
This paper studies how the effect of trade openness on economic growth may depend on complementary reforms that help a country take advantage of international competition. This issue is illustrated with a simple Harris-Todaro model where welfare gains after trade openness depend on the degree of labor market flexibility. The paper then presents cross-country, panel-data evidence on how the growth effect of openness may depend on a variety of structural characteristics. For this purpose, the empirical section uses a non-linear growth regression specification that interacts a proxy of trade openness with proxies of educational investment, financial depth, inflation stabilization, public infrastructure, governance, labor market flexibility, ease of firm entry, and ease of firm exit. The paper concludes that the growth effects of openness may be significantly improved if certain complementary reforms are undertaken.